THU0538 Association of Interleukin-27 Elevation with Abnormal B Cell Functions in Patients with Sjogren's Syndrome. (10th June 2014) - Zhang, L.; Zhao, C.; Liu, R.; Li, X.; Feng, X.; Sun, L.
Abstract : Background: Interleukin (IL)-27 is a new member of IL-6/IL-12 family involved in isotype switching and plasma cell differentiation of naïve B cells. Objectives: The objective of this study is to investigate the association of IL-27 with B cell functions in patients with Sjogren's syndrome (SS), an autoimmune disease characterized by B-cell hyperactivity. Methods: B cell activation was measured by the percentages of CD40 and CD69 positive cells in total CD19 + B cells under flow cytometry. Carboxyfluorescein diacetate succinimidyl ester (CFSE) and Annexin V were marked to detect B cell proliferation and apoptosis respectively. CD27 and CD138 were used to identify the trend of CD19 + B cell differentiation. To verify the role of IL-27 on B cell regulation, peripheral blood mononuclear cells (PBMCs) collected from SS patients and healthy controls were stimulated by B cell activators including anti-CD40, recombinant human IL-4, CpG-ODN and F(ab)2 goat anti-human IgM with or without the presence of IL-27 at the concentration of 50ng/ml. 72 or 96 hours later, cells were harvested and detected for B cell activation, proliferation, apoptosis and differentiation. Levels of several cytokines that have been reported to participate in B cell regulation, including IL-27, IFN-γ, IL-10, IL-4 and BAFF, were detected by ELISA. Results: Compared with healthy controls, the percentages of active B cells (CD40 or CD69 positive in total CD19 + B cells) were elevated in SS patients ( p both <0.05). B cells from SS patients displayed higher proliferation and apoptosis rate ( p both <0.05), and an increased cell differentiation into plasma cells was observed ( p <0.05). Serum levels of IL-27 were elevated in SS patients, especially in those with high titers of ANA (197.2±24.48 pg/ml vs. 179.8±9.37 pg/ml, p <0.01) or positive anti-SSA/SSB antibodies. In vitro cultures showed that IL-27 stimulation could increase the percentages of CD40/CD69 and CD138 cells, promote B cell proliferation and IgG secretion. Meanwhile, IL-27 could upregulate several B cell related factors in vitro (484.2±235.9 pg/ml vs. 4718±259.9 pg/ml for IFN-γ, 119.2±39.7 pg/ml vs. 98.58±29.17 for IL-4 and 1711±556.6 pg/ml vs. 1436±660.3 pg/ml for IL-10, p all <0.05). Conclusions: IL-27 elevation contributes to B cell hyperactivity in SS patients. Treatment targeting IL-27 may be promising for the amelioration of this disease. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2416